Frost resistance assessment for roof ceramic tile/Über die bestimmung der frostbeständigkeit keramischer dachziegel und ziegel - Sadūnas, Antanas; Mörtel, Heinrich; Cimmers, Andris; Švinka, Visvaldis; Būrė, Domas (Journal of Civil Engineering and Management, 2000)
Up today in Europe there is no unanimous opinion which method is necessary for a correct assessment of roof ceramic tile frost resistance corresponding to the climatic conditions of application. Even the latest EU standards offer four methods of the assessment of the frost resistance for roof ceramic tile. Those standards refer to investigations carried out in various West Europe countries. Aluminosilicate laboratories of Vilnius Pedagogical University by cooperating with Erlangen-Nurenberg University and Riga Technical University have carried out investigation of roof ceramic tile frost resistance by applying two different methods (three-side and one-side freezing-thawing). Besides, deformations under one-side freezing-thawing and others physical-mechanical indices of the ceramic tile were investigated. Referring to the results of investigation of tiles manufactured by CO Lode (Latvia) and CO “Palemono keramika” (Lithuania), we have proved that three-side freezing-thawing method is erroneous for estimating frost resistance of the roof ceramic tile. Research of frost resistance of roof tile and brick is carried out at three research institutes. Tiles were tested using one-side and three-side (volume) freezing. In addition, rapid frost resistance evaluation method was determined using deformation measurement under cyclic frost-thawing process, textures and water adsorption, saturation coefficient under boiling conditions or vacuum environment of the samples tested. One-side freezing-thawing method using water or artificial rain for thawing of samples was determined as the mostly suitable testing method. Distribution of sizes of pores and capillars was determined as not tightly bound. The equations 2 and 4 indicate the possibility to forecast frost resistance of roof tile by two physical parameters: deformation size and water coefficient saturation in vacuum. Frost resistance of solid brick in one-sided freezing-method corresponds to the service conditions in brick walls better than for roof tile. Rapid forecast of frost resistance of solid brick is possible by the use of four physical parameters according to Equation 5.Apie keraminių čerpių ir plytų atsparumo šalčiui nustatymąSantrauka. Iki šiol nei Vakarų, nei Rytų Europoje dar nėra bendro požiūrio į čerpių, o iš dalies ir į plytų atsparumo šalčiui nustatymo būdą jis nepažengė toliau už Europos standarto projeką. Jame siūlomi net keturi variantai, kaip nustatyti čerpių atsparumą šalčiui. Tačiau vis labiau linkstama čerpių atsparumą šalčiui nustatyti jas šaldant iš vienos pusės. Iš greitų keraminių dirbinių atsparumo šalčiui prognozavimo metodų dažnai orientuojamasi į tuos, kai nustatomos pavienės čerpių fizikinės savybės: vandens įmirkis, įsotinimo koeficientas, porų ir kapiliarų pasiskirstymas medžiagoje pagal jų dydį ir kai kurie kiti rodikliai. Tačiau tai netenkina nei mokslininkų nei statybininkų praktikų. Todėl aktualu toliau tirti atsparumo šalčiui vertinimo kriterijus. Trijuose institutuose ištirtos dviejų AB čerpių bei vienos AB pilnavidurių gerai išdegtų plytų atsparumas šalčiui. Nustatyta, kad vienpusis šaldymo ir atitirpinimo metodas artimesnis čerpių o ypač plytų, eksploatacinėms sąlygoms (tūrinio šaldymo atžvilgiu). Atsparumo šalčiui neįmanoma prognozuoti pagal kurį nors vieną šukės fizikinį rodiklį (pvz., pagal porų pasiskirstymo pagal dydį duomenis). Geriau tinka prognozė pagal kelis fizikinius keraminių dirbinių savybių rodiklius.Article in German.First Published Online: 26 Jul 2012